Efeito de antidepressivos sobre as enzimas envolvidas no controle da sinalização purinérgica e colinérgica em cérebro de peixe-zebra (Danio rerio) - Oliveira, Renata da Luz (2012)
The clinical depression treatment faces serious obstacles as the disease mechanism is not fully elucidated. In addition, there are no effective means to predict and prevent depression as well as any biological method of diagnosis. The use of antidepressants is still the basis of the treatments for depression. Lithium has been used clinically as effective drug to treat all phases of bipolar disorder, including major depression. The Selective serotonin re-uptake inhibitors (SSRIs), such as fluoxetine and citalopram, and Tricyclic antidepressant (TCA) as clomipramine are drugs constantly used for depression treatment. Recent evidence has shown an involvement of adenosine and its receptors in the pathophysiology of depression. ATP can be stored and co-released with other neurotransmitters like serotonin and can be hydrolyzed by a cell-surface enzyme family known as ectonucleotidases. Among these members, we highlight the nucleoside triphosphate diphosphohtdrolases (NTPDases) and ecto-5'-nucleotidase. They are able to control the availability of ligands such as ATP and adenosine to its specific receptors. Adenosine deaminase (ADA) can promote the hydrolytic deamination of adenosine to inosine, modulating the extracellulr levels of this neuromodulator. In cholinergic signaling, after its release, acetylcholine (ACh) promotes the activation of specific muscarinic or nicotinic receptors and thus, it promotes diverse cellular responses. ACh is hydrolyzed by acetylcholinesterase (AChE) in acetate and choline in synaptic cleft. The zebrafish has been used in research behavioral neuroscience and is also a choice model for elucidating the development and function of neuronal circuitry. Considering the cholinergic and purinergic signaling are important participation in the CNS and these neurotransmitter pathways have been identified and characterized in zebrafish, the objective of this study was to evaluate the effect of antidepressants on ectonucleotidases, ADA and ACh activities, which are essential enzymes in the modulation of these signaling pathways in the zebrafish brain. We evaluated the ex vivo effects of fluoxetine (1-10 μM), clomipramine (1-10 μM), citalopram (70-300 μM) on ectonucleotidases and ADA activities. It has been also analyzed the in vitro (1 to 1000 μM) and ex vivo (1 to 10mg/L) effect of lithium on ectonucleotidases and AChE activities and gene expression. There was a significant inhibition of ADP hydrolysis after ex vivo exposure to lithium at 5 and 10 mg/L, whereas an inhibitory effect was observed for AMP hydrolysis only at 10 mg/L. The same treatment decreased the AChE activity in a concentration of 10mg/L. Lithium did not induce significant changes in the analysis of gene expression patterns in the concentrations tested. In vivo treatment, there were no significant changes inectonucleotidases and AChE activities. Treatment with clomipramine promotes an inhibition ecto-5'-nucleotidase activities at the concentration of 5μM when compared to the control group. For ADA activity, we also observed a significant inhibition in the treatment with clomipramine at concentrations of 5 and 10 μM in membrane fractions of zebrafish brain. However, treatment with fluoxetine and citalopram did not alter ectonucleotidases and ADA activities in the zebrafish brain. Our findings may contribute to a better understanding of pharmacology of antidepressants and their interaction with the cholinergic and purinergic neurotransmission.